Management of C-shaped canals using "Membrane-Barrier Technique": a case report / Afzan Adilah Ayoub and Gary Shun-Pan Cheung - Ayoub, Afzan Adilah; Cheung, Gary Shun-Pan (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
A 61-year old Chinese female was referred from a general private practitioner for persistent buccal abscess after completion of root canal treatment of tooth 37. On clinical examination, tooth 37 presented with a metal-ceramic crown (CMC) with 2mm of gingival recession noted at the buccal region. The overlying amalgam core was overhanging on distal and grade 2 mobility. The 37 CMC have no contact point at the distal. Tooth 37 was not tender to palpation but tender to percussion. No periodontal pocketing was detected. The periapical radiograph revealed a periapical radiolucent area associated end of its root. These 37 apices were resorbed, probably a result of the apical periodontitis there. Widening of periodontal space was noted with this 37. A diagnosis of chronic apical periodontitis with external resorption of root apices with a C-shaped canal was made for the tooth 37. Membrane barrier technique with MTA was used for obturation. A bonded amalgam core was placed in this tooth.